Relationship Between Characteristic and Hypertension With Incidence of Ischemic Stroke - Siti Rohmatul Laily (Universitas Airlangga, 2017)
Stroke is a disease caused by circulatory disorders of the brain that is influenced by several risk factors that can not be changed such as age and sex or can be changed such as hypertension, diabetes mellitus, dyslipidemia, and work. This study aims to determine the relationship of characteristics and hypertension with the incidence of ischemic stroke in the Regional Public Hospital (RSUD) Ngimbang Lamongan in 2016. The design of this study was observational analytic with a case-control study design. Case samples were ischemic stroke sufferers, while control samples were non-ischemic strokes, each with 44 respondents. The sampling technique uses simple random sampling. Collecting data through secondary data using medical record data. The statistical test used was the chi-square test. The results showed a significant relationship between age (p = 0.015; OR = 3.286; 95% CI = 1,332–8,107), gender (p = 0.001; OR = 4,765; 95% CI = 1,912–11,875), employment status (p = 0.001; OR = 4,667; 95% CI = 1,890–11,526), and hypertension (p = 0,000; OR = 129,000; 95% CI = 15,848–1050,034) with ischemic stroke. The conclusion of this study there is a relationship between age, sex, work status, and hypertension with the incidence of ischemic stroke in Ngimbang Lamongan District Hospital in 2016.